"Heavy-atom effects" in the parent [1]benzochalcogenopheno[3, 2-b][1]benzochalcogenophene system. Issue 43 (4th June 2020) - Wang, Chengyuan; Abbas, Mamatimin; Wantz, Guillaume; Kawabata, Kohsuke; Takimiya, Kazuo
Abstract : Effects of the chalcogen atoms in [1]benzochalcogenopheno[3, 2- b ][1]benzochalcogenophenes (BXBXs), the key π-conjugated core structures in the development of superior organic semiconductors, are investigated. Abstract : [1]Benzochalcogenopheno[3, 2- b ][1]benzochalcogenophenes (BXBXs) have been the key π-conjugated core structures in the development of superior organic semiconductors for organic field-effect transistors (OFETs). The semiconducting properties of parent BXBXs, however, have not been well examined. In this work, we focus on the parent system and investigate the effect of different chalcogen atoms, i.e., sulphur, selenium or tellurium atoms, in the BXBX core on molecular electronic properties, crystal structures, intermolecular interactions, solid-state electronic structures, and carrier transport properties. Replacing the sulphur atoms in [1]benzothieno[3, 2- b ][1]benzothiophene (BTBT ) with selenium atoms marginally changes the molecular properties and the intermolecular interactions, thus resulting in similar herringbone packing structures in the solid state. The carrier mobilities of single-crystal (SC)-OFETs are higher for [1]benzoselenopheno[3, 2- b ][1]benzoselenophene (BSBS ) than those for BTBT, which can be understood by the increase in the intermolecular electronic coupling in BSBS, originating from the larger atomic radius and more diffused electron cloud of selenium atoms than sulphur atoms. On the other hand, the packing structure of [1]benzotelluropheno[3, 2- b ][1]benzotellurophene (BTeBTe ) is determined to be a dimeric herringbone structure. The crystal structure of BTeBTe being strikingly different from those of BTBT and BSBS can be explained by a drastic change in the intermolecular interaction in the solid state. Furthermore, the BTeBTe -based SC-OFETs do not show transistor response. To elucidate these unexpected results, various experimental and theoretical approaches, e.g., evaluation of ionization potentials and band calculations, are examined. Through these approaches, a comprehensive view of the parent BXBX system is given, and also both the pros and cons of incorporation of heavy chalcogen atoms, positive and negative "heavy-atom effects", in developing organic semiconductors are discussed.